2002
DOI: 10.1094/pdis.2002.86.4.418
|View full text |Cite
|
Sign up to set email alerts
|

Species Delimitation and Host Specialization of Ceratocystis laricicola and C. polonica to Larch and Spruce

Abstract: Ceratocystis laricicola and C. polonica are fungal symbionts of bark beetle species of the genus Ips that attack species of Larix and Picea, respectively, across Eurasia. Earlier studies found that these fungal species were morphologically identical, had similar isozymes patterns, and had identical internal transcribed spacer (ITS) sequences of the rDNA operon. We analyzed 27 isolates from Europe, southwestern Siberia (Russia) and Japan, representing the known geographic ranges of the two species. Phylogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 20 publications
5
28
0
Order By: Relevance
“…Although some of the Brazilian populations were highly differentiated from each other, mating studies indicated that they constitute a single biological species that is interfertile with C. fimbriata from sweet potato on which the species is based (Engelbrecht & Harrington, 2005). By contrast, crosses between different species of Ceratocystis produce no interaction when paired, or they form only a few perithecia with few ascospores that are misshapen, germinate poorly and produce colonies of aberrant morphology and aberrant segregation of markers (Harrington & McNew, 1997; Harrington et al. , 2002; Engelbrecht & Harrington, 2005; Johnson et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some of the Brazilian populations were highly differentiated from each other, mating studies indicated that they constitute a single biological species that is interfertile with C. fimbriata from sweet potato on which the species is based (Engelbrecht & Harrington, 2005). By contrast, crosses between different species of Ceratocystis produce no interaction when paired, or they form only a few perithecia with few ascospores that are misshapen, germinate poorly and produce colonies of aberrant morphology and aberrant segregation of markers (Harrington & McNew, 1997; Harrington et al. , 2002; Engelbrecht & Harrington, 2005; Johnson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures were observed for 4 weeks for the presence of perithecia and ascospore masses. Ascospore masses were examined microscopically (×400) to see if there were abundant, normal‐appearing ascospores (indicative of an interfertile cross) or if there were few or no ascospores, or if the ascospores were misshapen, which is typical of an interspecific cross or hybrid (Harrington & McNew, 1998; Harrington et al. , 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Isolates of C. polonica associated with I. typographus in Europe and I. typographus japonicus in Japan are morphologically indistinguishable (Y amaoka et al. 1997), interfertile with each other (H arrington et al. 2002) and phylogenetically closely related (H arrington et al.…”
Section: Introductionmentioning
confidence: 99%
“…1997), interfertile with each other (H arrington et al. 2002) and phylogenetically closely related (H arrington et al. 2002; M arin et al.…”
Section: Introductionmentioning
confidence: 99%
“…Bark beetles that infest conifers carry many different ophiostomatoid fungi including those related to Ophiostoma (Jacobs and Kirisits 2003;Kim et al 2003;Zhou et al 2004Zhou et al , 2006Kirisits 2007;Romon et al 2007;Linnakoski et al 2008Linnakoski et al , 2009Masuya et al 2009;Jankowiak and Kolarik 2010;Linnakoski et al 2010;Paciura et al 2010) and Ceratocystis (Harrington and Wingfield 1998, Harrington et al 2002, van Wyk et al 2004, Viiri and Lieutier 2004, Reid et al 2010. Although many of these fungi have the ability to cause lesions when inoculated into conifers (e.g.…”
Section: Introductionmentioning
confidence: 99%